A survey of work environment inhibitors to informal workplace learning activities amongst Malaysian accountants - Abdul Wahab, Muhammad Syahir; Saad, Ram Al Jaffri; Selamat, Mohamad Hisyam (Elsevier Ltd., 2014)
A survey was conducted to examine informal workplace learning activities and work environment inhibitors to such learning activities of accountants in public accounting firms across Malaysia.The findings indicated that the accountants use a variety of informal learning activities, although meeting predominates.The accountants reported that lack of time due to heavy workload, lack of meaningful rewards, lack of fund, limited influence on firm's operation and lack of support from others as the inhibitors to the learning activities.Theoretical and practical implications of the study as well as suggestions for future research were also discussed.